2004
DOI: 10.1023/b:nody.0000042910.39609.f6
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Motion and Stability of a Class of Discontinuous Dynamical Systems

Abstract: Abstract. A closed container with gas and liquid inflows and one outlet for outflow, described by a nonlinear hydraulic model, is shown to reach a state of sliding mode. Through a Lyapunov function, the sliding motion is shown to be stable for all positive exponents in the flow model. This property is independent of factors, such as, valve opening, valve coefficients, friction factor and initial states, making this device a suitable one to study two phase flow. The sliding solution of this system with square r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is assumed that the liquid and the gas are ideal. The total accumulation of each component in the reactor is the sum of it in the two phases: this is expressed by (7) and (8). Finally, (9) and (10) express the fact that the liquid and the gas phases are in equilibrium.…”
Section: Discontinuous Mode Of Operation Of Hdpe Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that the liquid and the gas are ideal. The total accumulation of each component in the reactor is the sum of it in the two phases: this is expressed by (7) and (8). Finally, (9) and (10) express the fact that the liquid and the gas phases are in equilibrium.…”
Section: Discontinuous Mode Of Operation Of Hdpe Reactormentioning
confidence: 99%
“…It is well known that there is usually quite a bit of measurement error in experiments involving two phase flow. Through Lyapunov function, it has been shown that the state of sliding is stable so long as the outflow and pressure drop have a monotonic relationship: that is, both of them increase or decrease simultaneously [8]. This stability property is independent of factors, such as, valve opening, valve coefficient, friction factor and starting points.…”
Section: Experimental Validation Of Sliding Phenomenonmentioning
confidence: 99%